An R package for climate forecast verification. (May 2018) - Manubens, Nicolau; Caron, Louis-Philippe; Hunter, Alasdair; Bellprat, Omar; Exarchou, Eleftheria; Fučkar, Neven S.; Garcia-Serrano, Javier; Massonnet, François; Ménégoz, Martin; Sicardi, Valentina; Batté, Lauriane; Prodhomme, Chloé; et al.
Abstract: Forecast verification is necessary to determine the skill and quality of a forecasting system, and whether it shows improvement with pre- or post-processing. s2dverification v2.8.0 is an open-source R package for the quality assessment of climate forecasts using state-of-the-art verification scores. The package provides tools for each step of the forecast verification process: data retrieval, processing, calculation of verification measures and visualisation of the results. Examples are provided and explained for each of these stages using climate model output. Highlights: An R package that streamlines the entire verification process is presented. A range of verification scores can be applied directly to multi-model ensembles. Plotting functions allow the rapid visualization and interpretation of results. Sophisticated bias correction methods are included.